Concept of Illegal Fishing for Indonesian Regulations and UNCLOS - Karina Tri Ambarsari; Ilham Rahmansyah; Andi Muhammad Fajar Abidin; Aurellya Desita Ananda Putri (Yuridika, 2023)
Illegal fishing is a transnational crime that needs special attention in its eradication to safeguard national sovereignty. Illegal fishing law enforcement and the protection of marine assets in Indonesia are based on the Shipping Law, Fisheries Law, Ministerial Regulations, and UNCLOS. Must be protected by any actions related to opportunities for crime to occur. There is no legal protection for potential geographical indications as a communal right of the people in Indonesia. This paper adopted the normative method with data sources drawn from primary and secondary legal materials. In addition, control practices are important in the fight against illegal, unreported, and unregulated (IUU) fishing. From here, the sinking of the ship became one of the control programmes. The current perspective on the problem of sinking or destroying fishing vessels is not from a legal aspect but from a standard or guideline for implementing procedures that have not been regulated, even though the Indonesian government is the subject of comparison with applicable laws.